Blood biochemical abnormalities of intensive care unit patients with SARS-CoV-2 infection, single center experience in Bangladesh - Naznin, Bidoura; Ghosh, Mousumi; Rabbani, Raihan; Yesmin, Israt; Rahman, Arebia (International Journal of Advances in Medicine, 2021)
Background: Since its emergence, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has spread worldwide, and led to ever-increasing mortality. SARS-CoV-2 infection perturbs the function of the body’s vital organs, making patients of all ages susceptible to the disease. Nevertheless, individuals developing critical illness with poor outcomes were mostly the elderly and people with co-morbid conditions, who constituted the vast majority of coronavirus disease 2019 (COVID-19) fatalities. Complications of COVID-19 mostly involve the respiratory, renal and cardiovascular systems, and in severe cases secondary infections leading to pneumonia and acute respiratory distress syndrome, which may precede the death of the patient. Multi-organ failure in individuals with COVID-19 could be a consequence of their co-morbidities. It is hoped that the review will lead to more comprehensive understanding of this complex disease. The aim of the study was to evaluate biochemical abnormalities during SARS-CoV-2 infection of ICU patients. Methods:This observational study was conducted in Square Hospital Limited, Dhaka, Bangladesh, on 50 patients received ICU treatment with moderate to severe COVID-19 symptoms admitted to this hospital from 15 July to 15 September 2020. Results: Among the participants most of them were 19 (38%) belongs to 65-74 years age group male 38 (78.00%) were dominating the gender distribution. IL6, CRP, creatinine and troponin were found the most significant in biochemical blood parameters. The maximum level of comorbidity was observed due to diabetes mellitus, ischemic heart disease, and hypertension. Conclusions:Biochemical parameters may be used as an indicator of COVID-19 infections and the severity of ICU patients. For the consistency of the course of patients, the markers could be used.